Home Sweet Home - Putri, Chintia Renata; Mansyur, Herlinda (Universitas Negeri Padang, 2024)
The creation of Home Sweet Home dance works aims to express feelings or expressions in the form of motion so as to realize creative dance works and can express ideas inspired by the life of the stylist as a girl. This Home Sweet Home dance work is inspired by the phenomenon of the dance director's own family life. Describe how a girl who has a single parent or single parent feels. Home Sweet Home is a term nowadays that means my house, my palace, which tells about how bitter sweet life is in the family of stewards. Every family has its own problems, one of which is that a husband leaves his family and imposes all the dependents and problems on a wife, so that a mother bears a lot of burden in the family. A child who feels and witnesses his own family conflicts certainly has mixed and confused feelings. So from the child's feelings, it is raised into a work that is conveyed through motion media. The work of HOME SWEET HOME is a dramatic dance whose symbolic performance form is representative realized through movement, decoration, makeup, clothing, lighting and reinforced with music.